The national system of innovation concept: An ontological review and critique - Manzini, Sibusiso (South African Journal of Science, 2012)
The construct 'national system of innovation' (NSI) is used to characterise a country's collective efforts towards fostering technological innovation. Since appearing in the 1996 White Paper on Science and Technology, the term has been used widely in South African policy discourses.This study makes a contribution towards an increased understanding of the meaning and implications of the NSI as a policy construct. The preponderant themes that emerge from this analysis underline the importance of fostering quality networks within the NSI. The NSI philosophical framework provides a solid foundation for organising the country's collective efforts in science and technology in a much more integrated and holistic fashion. Innovation policies and plans should aim to bring about synergy within the various elements of the NSI, particularly within small developing economies such as South Africa, in order to build robust innovation-driven economies.